2017
DOI: 10.3389/fpsyg.2017.00433
|View full text |Cite
|
Sign up to set email alerts
|

The Acquisition of Orthographic Knowledge: Evidence from the Lexicality Effects on N400

Abstract: This study aimed to understand how reading ability shapes the lexicality effects on N400. Fifty-three typical developing children from the second to the sixth grades were asked to perform the pronounceability judgment task on a set of Chinese real characters (RC), pseudocharacters (PC) and non-characters (NC), as ERPs were recorded. The cluster-based permutation analysis revealed that children with low- to medium-reading ability showed greater negativity to NCs than to RCs and PCs in frontal sites from 300 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…We used language control measures (i.e., N2 and LPC) as predictors of behavioral measures of executive control (i.e., RT). All continuous variables were centred by z ‐score transformation of raw scores to reduce collinearity (Tzeng, Hsu, Huang, & Lee, 2017). In addition, in order to avoid error detection in the language control trials affecting flanker trials, we only included correct flanker trials that were preceded by a correct language‐trial response.…”
Section: Resultsmentioning
confidence: 99%
“…We used language control measures (i.e., N2 and LPC) as predictors of behavioral measures of executive control (i.e., RT). All continuous variables were centred by z ‐score transformation of raw scores to reduce collinearity (Tzeng, Hsu, Huang, & Lee, 2017). In addition, in order to avoid error detection in the language control trials affecting flanker trials, we only included correct flanker trials that were preceded by a correct language‐trial response.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have found that the frontal‐based N400‐like component is directly related to the processing of orthographic representation, rather than the mapping of subcharacter representations onto whole character orthographic representation (Dong et al, 2015) or mapping the phonology to orthography of Chinese characters (Wu & Deng, 2011). The higher the degree of mismatch between the presented stimulus and the orthographic knowledge of Chinese characters, the N400‐like component in the frontal sites likely becomes more negative (Tzeng et al, 2017; Tzeng et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that a decrease in N400 amplitude may reflect easier access to lexico-semantic information (Almeida, 2021; Kutas & Federmeier, 2000; Lau et al, 2009; Meade et al, 2019). The amplitude of N400 has been shown to be larger for pseudowords than words, and this effect has been identified in various paradigms – semantic categorization (Coch & Benoit, 2015), the lexical decision task (Braun et al, 2006; Carreiras et al, 2005), the silent reading task (Bermúdez-Margaretto, Shtyrov, et al, 2020), the pronounceability judgment task (Tzeng et al, 2017). In addition, the N400 wave is associated with phonological processing and is traditionally considered in works with pseudohomophones, in which a less negative wave reflects higher activation of a particular phonological representation (Barnea & Breznitz, 1998; Briesemeister et al, 2009; Costello et al, 2021; González-Garrido et al, 2015; Y.…”
Section: Discussionmentioning
confidence: 99%